2021
DOI: 10.1021/acsomega.0c05318
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Biochemical Determinants of Protein Degradation Rates

Abstract: Protein degradation is a key component of the regulation of gene expression and is at the center of several pathogenic processes. Proteins are regularly degraded, but there is large variation in their lifetimes, and the kinetics of protein degradation are not well understood. Many different factors can influence protein degradation rates, painting a highly complex picture. This has been partially unravelled in recent years thanks to invaluable advances in proteomics techniques. In this Mini-Review, we give a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Protein lifetime can be influenced by both sequence‐encoded features and environmental factors (Marrero & Barrio‐Hernandez, 2021 ). For instance, proteins with long disordered segments are generally more short‐lived than proteins that adopt a stable structure (van der Lee et al , 2014 ; Fishbain et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Protein lifetime can be influenced by both sequence‐encoded features and environmental factors (Marrero & Barrio‐Hernandez, 2021 ). For instance, proteins with long disordered segments are generally more short‐lived than proteins that adopt a stable structure (van der Lee et al , 2014 ; Fishbain et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we determined the kinetics of degradation by this concatenated degron. In general, the ubiquitin-proteasome system (UPS) can react fairly quickly to the changing environment and can degrade targeted proteins in a matter of minutes. Ideally, a system of inducible degradation of proteins can take advantage of this property of UPS and allow similarly fast degradation and thus enable rapid temporal control of protein stability. We observed that the substrate degradation using concatenated SSD degron was very fast at higher concentrations of rapamycin, achieving near-plateau levels after only 30 min (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the N-terminus is generally evolutionarily optimized for expression efficiency, which also supports why it is widely used for protein expression optimization [86][87][88] . A short hotspot at the very last position in the C-terminus was frequently mutated, which is known as a signal involved in protein degradation 5,6 . Besides the Cterminus, however, most of the amino acids were substituted uniformly across the entire sequence length, mainly with the hydrophobic amino acids A (alanine), G (glycine) and V (valine) (Figure 2G).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, protein synthesis is strongly regulated at the initiation step 1,2 , whose rate varies broadly between mRNAs, depending not only on the transcript sequence features but also on the amino acids at the N-terminal 3,4 . In bacteria, the amino acid composition of the C-terminal is a strong determinant of protein degradation rates, explaining a wide range of protein abundances 5,6 . These, along with the multiple mechanisms of post-translational regulation 7,8 , suggest that this rather tight regulation occurs at the degradation level and is encoded, at least partially, in the amino acid sequence.…”
Section: Introductionmentioning
confidence: 99%